A pulse-chase epitope labeling to study cellular dynamics of newly synthesized proteins: a novel strategy to characterize NPC biogenesis and ribosome maturation/export - Stelter, Philipp; Hurt, Ed (Nuclear pore complexes and nucleocytoplasmic transport, 2017)
The vast number of cellular proteins performs their roles within macromolecular assemblies and functional cell networks. Hence, an understanding of how multiprotein complexes are formed and modified during biogenesis is a key problem in cell biology. Here, we describe a detailed protocol for a nonradioactive pulse-chase in vivo-labeling approach. The method is based on the incorporation of an unnatural amino acid (O-methyl-tyrosine) by the nonsense suppression of an amber stop codon that quickly fuses an affinity tag of choice to a protein of interest. This affinity tag could be used to directly isolate the newly synthesized proteins and hence allows for the characterization of early complex biogenesis intermediates. Combined with a tetracycline controllable riboswitch in the 5′-UTR of the respective mRNA, this approach became a versatile tool to study dynamic protein assembly within cellular networks (Stelter et al., 2012). In the context of this volume, this method notably provides a suitable approach to study NPC, ribosome and mRNP biogenesis, or nuclear protein translocation. This chapter includes detailed protocols to track newly synthesized, epitope pulsed-chased proteins by western blot, their assembly within complexes using immunoprecipitation, and their subcellular localization using indirect immunofluorescence or subcellular fractionation. While these protocols use budding yeast as model system, this method can be adapted to other model systems.
Gesehen am 30.09.2020